2010
DOI: 10.1007/s12526-010-0058-8
|View full text |Cite
|
Sign up to set email alerts
|

The pan-Arctic biodiversity of marine pelagic and sea-ice unicellular eukaryotes: a first-attempt assessment

Abstract: Arctic marine unicellular eukaryotes are composed of microalgae and non-autotrophic protists. These eukaryotes comprise a well-diversified group of organisms that are either adapted to live in the upper water column of coastal and oceanic regions, here defined as phytoplankton/ pelagic communities, or in bottom horizons of sea ice and known as sympagic/sea-ice-associated communities. There are approximately 5,000 recognized legitimate marine phytoplankton species and an unknown number of sympagic eukaryotes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
199
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(224 citation statements)
references
References 61 publications
24
199
1
Order By: Relevance
“…Several studies have reported the presence of either Protoceratium reticulatum or YTX in mussels in the Arctic Ocean (Okolodkov, 2005;Vershinin et al, 2006;Poulin et al, 2011). The Greenland isolates of P. reticulatum, as verified by detailed morphologic and phylogenetic analysis, are the first isolates grown in culture of this species from arctic waters.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several studies have reported the presence of either Protoceratium reticulatum or YTX in mussels in the Arctic Ocean (Okolodkov, 2005;Vershinin et al, 2006;Poulin et al, 2011). The Greenland isolates of P. reticulatum, as verified by detailed morphologic and phylogenetic analysis, are the first isolates grown in culture of this species from arctic waters.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, range extension of phytoplankton taxa responsible for HABs and toxin production into and within the Arctic are to be expected. In the past, a number of harmful eukaryotes have been recorded in marine plankton and sympagic communities across the entire Arctic region, with the domoic acid producing planktonic diatoms Pseudo-nitzschia delicatissima, Pseudo-nitzschia pungens and Pseudo-nitzschia seriata, the prymnesiophyte Phaeocystis pouchetii, and the dinoflagellates Azadinium sp., Amphidoma languida, Alexandrium tamarense, Alexandrium ostenfeldii, Dinophysis acuminata, Dinophysis acuta, Dinophysis norvegica, Gonyaulax spinifera, and Protoceratium reticulatum as the most abundant species (Okolodkov, 2005;Poulin et al, 2011;Tillmann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sea ice provides a vast habitat for productive microbial communities consisting of algae, bacteria, archea, heterotrophic protists, funghi as well as viruses [Horner et al 1992;Deming et al, 2010;Thomas and Dieckmann, 2010;Poulin et al, 2011]. Distinct communities are found at the base, in the interior and at the surface of ice floes [see, Horner, 1985;Arrigo et al, 2010].…”
Section: Organic Carbon Processes In Sea Icementioning
confidence: 99%
“…-Arctic planktonic protists account for over 2106 species (Poulin et al 2011). Hop et al (2006) reported a total of 148 taxa, of which Bacillariophyta (45%) and Dinophyta (11%) were the dominant groups in Kongsfjorden (Table 3).…”
Section: Primary Producersmentioning
confidence: 99%
“…This community develops through three distinct phases in the transition from winter to spring, which is described by Leu et al (2015). A total of 1027 sympagic protist taxa have been reported from four PanArctic regions (Syvertsen 1991;Poulin et al 2011). The biomass of ice algae communities is almost exclusively dominated by the genera Nitzschia, Navicula, Pauliella and Fragilariopsis (Gosselin et al 1997;Riedel et al 2008;Leu et al 2015), which often account for >90% of the total algal cell abundance (Smith and Sakshaug 1990; von Quillfeldt 2000; Różańska et al 2009;Wiktor 2015).…”
Section: Primary Producersmentioning
confidence: 99%